Hubungan posisi duduk terhadap keluhan nyeri punggung pada pengemudi angkutan umum - Shahrani Dwanti Pane; Tri Niswati Utami (Holistik Jurnal Kesehatan, 2023)
Background: Public transport drivers work 1 day in a sitting position for long working hours. The wrong sitting position for public transport drivers will cause back pain and interfere with work.Purpose: To determine the relationship between sitting position and back pain complaints and the causes of back pain complaints in public transport drivers.Method: Quantitative observational analytics with cross-sectional study design. This research was conducted in Medan Area District, Medan City, on public transportation 53 which was carried out in November 2022. The population in this study were all drivers of transportation number 53 Medan City totaling 120 respondents. The sample in this study uses a probability sampling technique in which every bus driver has the same opportunity to be the sample. Data collection techniques in this study used a questionnaire. Data analysis was performed using univariate and bivariate tests with chi-square.Results: It is known that there is no significant relationship between working hours p-value 0.446 (> 0.05) and there is a significant relationship between working hours and sitting position with complaints of back pain, working hours p-value 0.042 (<0.05) and sitting position p-value 0.000 (<0.05).Conclusion: There is a significant relationship between working hours and sitting position with complaints of back pain with a p-value <0.05. And there is no relationship between the length of work and complaints of back pain with a p-value > 0.05.Keywords: Sitting Positions; Back Pain; Driver; Public Transportation.Pendahuluan: Pengemudi angkutan umum bekerja 1 harian dengan posisi kerja duduk dengan waktu kerja yang lama, posisi duduk yang salah pada pengemudi angkutan umum akan mengakibatkan nyeri pada punggung dan mengganggu pekerjaan.Tujuan: Untuk mengetahui hubungan posisi duduk terhadap keluhan nyeri punggung dan penyebab keluhan nyeri punggung pada pengemudi angkutan umum.Metode: Kuantitatif yang bersifat observasional analitik dengan desain studi cross sectional. Penelitian ini dilakukan di Kecamatan Medan Area, Kota Medan, pada angkutan umum 53 dilakukan pada bulan November 2022. Populasi dalam penelitian ini adalah seluruh pengemudi angkutan nomor 53 kota medan berjumlah 120 responden. Sample dalam penelitian ini menggunakan teknik probabiliti sampling dimana setiap supir angkot memiliki kesempatan yang sama untuk menjadi sample. Teknik pengumpulan data dalam penelitian ini mengguanakan kuisioner. Analisis data dilakukan dengan menggunakan uji univariat dan bivariat dengan chi-quare.Hasil: Diketahui bahwa tidak terdapat hubungan yang signifikan antara lama kerja p-value 0.446 (> 0.05) dan terdapat hubungan yang signifikan jam kerja dan posisi duduk dengan keluhan nyeri punggung, jam kerja p-value 0.042 (<0.05) dan posisi duduk p-value 0.000 (<0.05).Simpulan: Terdapat hubungan yang signifikan antara jam kerja dan posisi duduk dengan keluhan nyeri punggung dengan hasil p-value < 0.05. Dan tidak terdapat hubungan antara lama kerja dengan keluhan nyeri punggung dengan hasil p-value > 0.05.